Capturing microalgae within aerosols provides carbon capture bio-functionality - Elbaraa Elghazy; Matt M.J Davies; Nicholas T.H Farr; Cornelia Rodenburg; Jon R. Willmott; Jagroop Pandhal (Journal of CO2 Utilization)
Climate change due to the greenhouse effect poses arguably the greatest challenge to humanity. Addressing the sources of CO2 and reducing current atmospheric levels is the paramount task for scientists and engineers. Carbon capture with storage or utilization technologies are key to achieving this goal. Biological carbon fixation is an effective method of converting pollutant CO2 into usable biochemicals for industrial applications. Inspired by recent evidence that 95 % of CO2 from aerosol emissions from an Australian forest fire was captured by algae in the Southern Ocean, as well as the ability of algae to be transported within aerosols, we propose a novel technique for CO2 sequestration based on creating aerosols containing metabolically active cyanobacteria. Using aerosols as a microenvironment for Synechocystis cells enables a significant increase in gas-liquid-interfacial-surface-area while reducing the volume of water required. We utilize electron microscopy and hyperspectral microscopy to assess the effects of aerosolization and high CO2 concentrations on microbial cell viability. Additionally, we implemented highspeed imaging and oil immersion microscopy to determine the effectiveness of the aerosolization technique for forming aerosols and optimizing process parameters. We show that 1 % CO2 (v/v) is ideal for CO2 capture, where cell stress was minimized. Using cell densities of 1.2 × 108 cell/mL was the most efficient in terms of the number of cells aerosolized when compared to the input cell density. We report a 6-fold increase in carbon fixation rates (gCO2 g−1 biomass hr−1) over alternative popular cultivation techniques such as bubble columns.